"A Terrible Beauty is Born": Erskine Childers' The Riddle of the Sands, the Spy Thriller and Modern Identity. Issue 5 (4th July 2018) - Sandberg, Eric
ABSTRACT: Erskine Childers' 1903 The Riddle of the Sands represents a transition point between the invasion scare novel and the emerging espionage novel. One of its main contributions to the latter is its representation of "normal" people as they are caught up in events of historical significance. The amateur status of its spies, particularly the narrator Carruthers, both preserves them from the opprobrium of dishonest and dishonourable behaviour, and makes them suitable vehicles for the text's exploration of the ambiguities of modern identity. This ambiguity concerns both personal ethics and national allegiance, and it finds its fullest expression in the novel in the shifting landscapes in which the narrative is set. The Riddle of the Sands can thus be read as an early use of popular fiction forms to examine the complexities of twentieth-century subjectivity in light of changes in historical experience.